Influence of hydrochloric acid volume on the growth of titanium dioxide (TiO2) nanostructures by hydrothermal method - Abd Hamed, Noor Kamalia (Universiti Kebangsaan Malaysia, 2016)
Titanium dioxide (TiO2) with various morphologies has been successfully synthesized by a simple hydrothermal method at 150oC for 10 h using titanium butoxide (TBOT) as a precursor, deionized (DI) water and hydrochloric acid (HCl) on a fluorine-doped tin oxide (FTO) substrate. The influences of HCl volume on structural and morphological properties of TiO2 have been studied using x-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM), respectively. The result showed that several morphologies such as microsphere, microrods, nanorods and nanoflowers were obtained by varying the volume of hydrochloric acid. The crystallinity of titanium dioxide enhanced with the increasing of hydrochloric acid volume.